1991
DOI: 10.1530/jrf.0.0910207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of oxygen free radical on ovulation and progesterone production by the in-vitro perfused rabbit ovary

Abstract: The potential role of oxygen free radicals in hCG-induced ovulation was investigated using the free radical scavenging enzymes superoxide dismutase (SOD) and/or catalase with the in-vitro perfused rabbit ovary preparation. SOD (25 micrograms/ml) and SOD + catalase (25 micrograms/ml) significantly reduced the % of large follicles that ovulated during perfusion (P less than 0.005). Neither maturity nor degeneration of ovulated ova and follicular oocytes was affected by SOD and/or catalase. Progesterone concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 11 publications
2
45
0
2
Order By: Relevance
“…Furthermore, it was recently demonstrated that exposure to LH elevates ROS levels in ovarian follicles (39), and the suppression of ROS by superoxide dismutase in in vitro-perfused rabbit ovary preparations hinders ovulation (40). In this work we show that in vivo administration of broad-range scavengers of oxidative species such as BHA and NAC into the ovarian bursa of eCG/hCGtreated mice significantly reduces the rate of ovulation.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, it was recently demonstrated that exposure to LH elevates ROS levels in ovarian follicles (39), and the suppression of ROS by superoxide dismutase in in vitro-perfused rabbit ovary preparations hinders ovulation (40). In this work we show that in vivo administration of broad-range scavengers of oxidative species such as BHA and NAC into the ovarian bursa of eCG/hCGtreated mice significantly reduces the rate of ovulation.…”
Section: Discussionsupporting
confidence: 49%
“…Reactive oxygen species may be released in connection with follicle rupture, because inhibition of oxygen free radicals leads to inhibition of ovulation (17). Reactive oxygen species are thought to play a role in oocyte maturation (18).…”
Section: Follicular Glutathione S-transferasementioning
confidence: 99%
“…Furthermore, subcutaneous administration of a large dose (30 mg/kg) of native SOD but not H,O,-inactivated SOD also inhibited the ovulation by 40-50%. Recent study also revealed that SOD inhibited hCG-induced ovulation in an isolated perfused ovary of the rabbit [29]. Thus, the inhibition of hCG-induced ovulation by SM-SOD might principally be due to dismutation of superoxide radicals rather than nonspecific toxicity of the SM moiety.…”
Section: Discussionmentioning
confidence: 98%